Identity Politics and Conflict Issues among Farmers in Ibarapa Area of Oyo State: Implications for Food Security - Oladosu, Olufemi; Adeyeye, Adebowale Idowu; Omitola, Bolaji Olumuyiwa (Kashere Journal of Politics and International Relations, 2025)
Conflicts between pastoral Fulani herdsmen and arable crop farmers in the Ibarapa Area of Oyo State, Nigeria have become phenomenal and a recurring decimal in recent years. Crises have continued to escalate with consequences for food security in the region and particularly in the nation because of the comparative advantage for food production which the area enjoys. The polyglot nature of Ibarapa and its rich arable savannah land is a potential recipe for ethnic conflict. This study investigated the identity politics and issues underlying ethnic clashes and skirmishes, and their impact on agricultural productivity and communal co-existence. The study employed qualitative method of data collection. Secondary information was collected through a survey of extant literature and was analyzed qualitatively to assess the dynamics of conflicts arising from crop damage, cattle theft and rustling and other critical issues. Thematic analysis was carried out through content analysis. The findings showed that competition over scarce resources (land and water) primarily drives social exclusion, heightens conflicts and complicates reconciliation. The study found out that disruption in ethnic and economic relations drastically alter the balance of food production and food security. It concludes on a multifaceted approach to addressing the conflicts including proper resource management, promotion of equitable access to resources and inclusivity concern in social and agricultural policy formulation and implementation to promote food security and sustainable development.